Characterization of the environmental entering university - Chumbe Rodríguez, Aldo Christian (2021)
The COVID-19 pandemic has caused human beings to rethink their connection with nature, because this 21st century, even with the greatest approach to environmental issues worldwide, is also a reality that the attitudes of political and social leaders they are insufficient, which means that the balance with nature continues to be broken. Therefore, the importance of knowing the environmental attitudes of the student community, who will assume the reins of future national projects, including environmental ones. The purpose of this study is to identify the levels of environmental attitude in university students. The sample consisted of 128 subjects from the professional schools of Veterinary Medicine and Sports Sciences of a private university in Metropolitan Lima. The research has a quantitative approach and a comparative descriptive design. To measure environmental attitude, a Likert-type scale was applied. The results show that university students are located in the medium level of environmental attitude. There were no significant differences between the levels of environmental attitude according to sex or age [with the exception of professional school]. This scientific work allows other investigations to carry out quasi- experimental programs with a constructivist approach, based on the use of collaborative work that include semester periods, and thus generate a consolidation and / or increase in the environmental attitude of university students.